Analisis Pengaruh Posisi dan Perbedaan Waktu Pengasapan Terhadap Kualitas Se’i Ikan - Ut Jasron, Jahirwan; Rodrikuens Kefi, Alfonsus; Gusnawati, Gusnawati (Jurnal Inovasi Teknologi Terapan, 2024)
Fish is one source of animal protein that is widely consumed by the community, but fish also quickly decay after being caught and dying. Fish must be handled properly to keep them in a condition suitable for consumption within a day of being caught. One way to preserve fish is by smoking. The smoking process by using a smoking cabinet to determine the water content, ash content, and protein content that affects the quality of fish se'i by SNI using a temperature that is maintained to remain at 80 °C-100 °C in the position of arranging fish vertically and horizontally with a difference in smoking time for 60 minutes, 90 minutes and 120 minutes using kesambi wood charcoal as fuel at 60 to 120 minutes Vertical Position Water Content between 62.05% and 65.27%, horizontal position 54.27% to 58.98%. The ash content produced ranges from 4.93% to 5.36%; in the horizontal position, it is 5.12% to 5.58%. The protein content in the vertical position protein content produced fish ranges from 15.20% to 20.58%, and in the horizontal position ranges from 12.75% to 17.97% with vertical heat transfer of 4704.42 kW and horizontal of 2101.28 kW the better the position of the arrangement of the fish, the better the quality of the fish produced and if it is faster or longer Smoking time can affect the quality of fish by decreasing or increasing the amount after smoking at a particular time which is affected by the heat generated from the fuel.